The value of chlortetracycline for steers on winter bluestem pasture - Smith, E.F.; Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
Forty Hereford steers were divided into two groups of 20 each on the basis of weight. Each group was pastured in a 160-acre bluestem pasture on the Pringle Ranch near Rose, Kansas, Both groups were fed protein blocks and chlortetracycline was included in the blocks for one group, to supply about 70 mgs. per steer daily. The blocks were composed of primarily of soybean meal with 10% salt to limit intake. They were kept before the animals continuously during the first half of the trial but during the latter half were rationed to keep consumption of both groups at about the same level.
Keywords: Beef; Chlortetracycline; Winter bluestem; Intake; Protein blocks